Myeloid cells Limit Production of Antibody Secreting cells After Immunization in the Lymph Node - Fooksman, David R (2013)
Antibody secreting cell (ASC) expansion and survival are important processes in optimizing vaccines and controlling autoimmunity. The microenvironment of the medullary cords is positioned to control these key processes. Previously, we imaged and characterized ASC differentiation and migration by intravital microscopy in the lymph node (LN) by transferring and activating B cells expressing YFP only in the ASC compartment. In this study, we observed that YFP+ ASCs in the medullary cords migrated along myelomonocytic cells and arrested in contact with them. Acute ablation of myeloid cells using the human diphtheria receptor system (DTR) expressed in Lysmd1-cre positive cells increased ASCs and antibody production by 2 fold. Increases in ASC numbers were associated with cell proliferation based on Ki-67 staining, rather than reduced apoptosis, or changes in egress from the LN. Using DTR-mediated ablation targeted to Ccr2 expressing myeloid cells also generated increases in ASCs. In contrast, neither the depletion of Gr-1-positive cells with an antibody nor the ablation of cells using a cd11c- DTR resulted in any change in ASCs. IL-6 cytokine signaling can enhance ASC production and has been implicated in dampening ASCs in lupus mouse models through myeloid cells. Using mixed BM chimeras, we observed that IL-6 enhances ASC production, but IL-6 production was not required by myeloid cells to dampen ASCs in the LN. Inhibition of ASCs by these myeloid cells in the LN provides a new regulatory mechanism with implications for tuning antibody responses.